La recreación humorístico-paródica del juicio de la risa en El asno de oro de Apuleyo - Rojas, Irene (2004)
The next paper presents the epi ode of Lucius trial at the Festival of Laughter in the text The Golden Ass by the Latin writer Apuleius (125 d. C.). These scenes parody histrionic aspects of forensic speeches for comic effect. Lucius' adventure prepares the vision of the novelistic hero in agreement with the coronation-dethronement rite of the carnival king.